Investigation of antiphytovirus action of the drug "Dekonex-50 FF" for the prevention of cucumber mosaic virus - Tsvihun, Viktoriia; Mazur, Svitlana; Sus, Nazarii; Humeniuk, Iryna; Levishka, A.S.; Botsula, Oleksandr (Problems of Environmental Biotechnology, 2021)
The antiphytovirus action of preparation "Dekonex-50 FF" against cucumber mosaic virus was tested; the preparation is commonly used for disinfection of various materials and medical devices, surfaces in the premises, and sanitary equipment.